2020
DOI: 10.1016/j.ijscr.2019.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Emergency laparoscopic resection of spontaneous rupture of hepatocellular carcinoma: A case report

Abstract: HighlightsRuptured hepatocellular carcinoma is associated with a significant morbidity and very high mortality rate.Epigastric pain with hypovolaemic shock in addition to a raised serum alpha-fetoprotein can be suggestive of ruptured hepatocellular carcinoma.One staged laparoscopic surgery can be considered among hemodynamically stable candidates with no ongoing bleeding and good functional liver reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Beside the different number of enrolled patients, different criteria for patient selecting may also relate to the different results. It has been reported that minimally invasive treatment could be used for the tumor rupture ( 27 - 29 ) because it is able to alleviate the postoperative liver function. Although the data of long-term follow-up and large sample are absent, laparoscopic hepatectomy should be considered during emergency when the RHCC patient with less bleeding (stable vital signs) and small tumor located peripherally, since the treatment with a minimal invasion and shorter operation time can maximize the benefit of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the different number of enrolled patients, different criteria for patient selecting may also relate to the different results. It has been reported that minimally invasive treatment could be used for the tumor rupture ( 27 - 29 ) because it is able to alleviate the postoperative liver function. Although the data of long-term follow-up and large sample are absent, laparoscopic hepatectomy should be considered during emergency when the RHCC patient with less bleeding (stable vital signs) and small tumor located peripherally, since the treatment with a minimal invasion and shorter operation time can maximize the benefit of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,8,20,21 Although the laparoscopic approach to liver resection is well accepted in HCC, its use in ruptured cases has not been well defined. 22 In our cohort, more than half of the patients were initially managed with TAE, and half of these underwent subsequent treatment either by staged liver resection or other therapies, whereas the remaining patients did not receive any subsequent treatments. Onethird of our cohort was managed with immediate surgical intervention.…”
Section: Discussionmentioning
confidence: 94%